Strategi Penanggulangan Penyakit Sosial di Kabupaten Morowali - Yunruth H Marande; Abdi Sakti Walenta (Pusat Riset dan Inovasi Nasional, 2026)
Social problems in North Morowali Regency have escalated through increasing deviant behaviors such as drug abuse, juvenile delinquency, domestic violence, and the weakening of community social values. These issues not only threaten social stability but also hinder regional development and community welfare. This Community Service Program aims to formulate and implement strategies to address social problems through educational and participatory approaches. The methods applied include socialization, training, assistance, and evaluation involving village officials, community leaders, youth representatives, the Women and Child Protection Office, and the Regional Development Planning Agency. The results indicate that community understanding of social problems improved significantly through awareness sessions and group discussions. The training activities strengthened skills related to social communication, family resilience, and youth empowerment. Meanwhile, the assistance phase enhanced community-based program implementation, and the evaluation revealed behavioral changes and increased community involvement in maintaining a healthy social environment. Thus, the strategies implemented successfully foster sustainable collaboration for the prevention of social problems in North Morowali Regency.